B-1b Cells Secrete Atheroprotective IgM and Attenuate Atherosclerosis - Rosenfeld, Sam M. (Circ Res, 2015)
RATIONALE: B cells contribute to atherosclerosis through subset specific mechanisms. Whereas some controversy exists about the role of B-2 cells, B-1a cells are atheroprotective due to secretion of atheroprotective IgM antibodies independent of antigen. B-1b cells, a unique subset of B-1 cells that respond specifically to T cell-independent antigens, have not been studied within the context of atherosclerosis. OBJECTIVE: To determine whether B-1b cells produce atheroprotective IgM antibodies and function to protect against diet induced atherosclerosis. METHODS AND RESULTS: We demonstrate that B-1b cells are sufficient to produce IgM antibodies against oxidation specific epitopes (OSE) on LDL both in vitro and in vivo. Additionally, we demonstrate that B-1b cells provide atheroprotection after adoptive transfer into B and T cell deficient (Rag1(−/−)Apoe(−/−)) hosts. We implicate Id3 in the regulation of B-1b cells as B cell-specific Id3 knockout mice (Id3(BKO)Apoe(−/−)) have increased numbers of B-1b cells systemically, increased titers of OSE-reactive IgM antibodies, and significantly reduced diet-induced atherosclerosis compared to Id3(WT)Apoe(−/−) controls. Finally, we report that the presence of a homozygous SNP in ID3 in humans that attenuates Id3 function is associated with an increased percentage of circulating B-1 cells and anti-MDA-LDL IgM suggesting clinical relevance. CONCLUSIONS: These results provide novel evidence that B-1b cells produce atheroprotective OSE-reactive IgM antibodies and protect against atherosclerosis in mice, and suggest that similar mechanisms may occur in humans.